2020
DOI: 10.1017/s0033291720001506
|View full text |Cite
|
Sign up to set email alerts
|

Mentalization-based treatment for psychotic disorder: a rater-blinded, multi-center, randomized controlled trial

Abstract: Background Impaired mentalizing ability – an impaired ability to understand one's own and other people's behavior in terms of mental states – is associated with social dysfunction in non-affective psychotic disorder (NAPD). We tested whether adding mentalization-based treatment for psychotic disorder (MBTp) to treatment as usual (TAU) results in greater improvement in social functioning. Methods Multicenter, rater-blinded, randomized controlled trial. Eighty-four patients with NAPD were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 51 publications
1
17
0
1
Order By: Relevance
“…A recent, randomized-controlled trial found MBT-p led to significant improvements in social functioning at post-treatment and at 6-month follow up. Results further revealed a trend toward better performance on measures of mentalizing ability in the MBT-p group and an increased effectiveness of MBT-p in early psychosis versus prolonged psychosis [ 110 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…A recent, randomized-controlled trial found MBT-p led to significant improvements in social functioning at post-treatment and at 6-month follow up. Results further revealed a trend toward better performance on measures of mentalizing ability in the MBT-p group and an increased effectiveness of MBT-p in early psychosis versus prolonged psychosis [ 110 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…MBT‐p is an emerging treatment that has led to multiple case studies and initial research studies. However, in the first RCT conducted using MBT‐p, Weijers et al (2020a) found that while treatment as usual (TAU) and MBT‐p plus TAU both showed large, significant improvements in social functioning at the end of treatment, improvements in the MBT‐p group were superior, more robust, and remained significant at a 6‐month follow‐up.…”
Section: Introductionmentioning
confidence: 99%
“…Formal MBT‐p includes a treatment package that is 18‐month long and includes a combination of weekly group therapy and half‐hour individual session once per 2 weeks (Weijers et al, 2020a) offered on an outpatient basis. The dose of individual and group therapy is minimized in the formal MBT‐p approach to avoid overwhelming patients with mentalization interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Studies reporting impairments in the affective rather than cognitive components of mentalizing such as empathy ( Derntl et al, 2009 ; Montag et al, 2020 ) are less common and there is only a limited spectrum of performance-based approaches to measure them ( Bonfils et al, 2016 ). Yet, the improvement of affective mentalizing abilities is receiving increasing attention in psychotherapies for patients with schizophrenia ( Liotti and Gilbert, 2011 ; Lempa et al, 2013 ; Montag, 2015 ; Weijers et al, 2020 ), and valid and reliable instruments are needed in order to investigate their effectiveness.…”
Section: Introductionmentioning
confidence: 99%